CD38‐NADase is a new major contributor to Duchenne muscular dystrophic phenotype. Issue 5 (17th March 2022) - de Zélicourt, Antoine; Fayssoil, Abdallah; Dakouane‐Giudicelli, Mbarka; De Jesus, Isley; Karoui, Ahmed; Zarrouki, Faouzi; Lefebvre, Florence; Mansart, Arnaud; Launay, Jean‐Marie; Piquereau, Jerome; Tarragó, Mariana G; Bonay, Marcel; et al.
Abstract: Duchenne muscular dystrophy (DMD) is characterized by progressive muscle degeneration. Two important deleterious features are a Ca 2+ dysregulation linked to Ca 2+ influxes associated with ryanodine receptor hyperactivation, and a muscular nicotinamide adenine dinucleotide (NAD + ) deficit. Here, we identified that deletion in mdx mice of CD38, a NAD + glycohydrolase‐producing modulators of Ca 2+ signaling, led to a fully restored heart function and structure, with skeletal muscle performance improvements, associated with a reduction in inflammation and senescence markers. Muscle NAD + levels were also fully restored, while the levels of the two main products of CD38, nicotinamide and ADP‐ribose, were reduced, in heart, diaphragm, and limb. In cardiomyocytes from mdx/CD38 −/− mice, the pathological spontaneous Ca 2+ activity was reduced, as well as in myotubes from DMD patients treated with isatuximab (SARCLISA ® ) a monoclonal anti‐CD38 antibody. Finally, treatment of mdx and utrophin–dystrophin‐deficient ( mdx/utr −/− ) mice with CD38 inhibitors resulted in improved skeletal muscle performances. Thus, we demonstrate that CD38 actively contributes to DMD physiopathology. We propose that a selective anti‐CD38 therapeutic intervention could be highly relevant to develop for DMD patients. Synopsis: Duchenne muscular dystrophy (DMD) is characterized by muscle NAD + deficit and muscle Ca 2+ overload. In various dystrophic mouse models and a human DMD cell culture, we have targeted the multifunctional enzyme CD38, a NAD + glycohydrolase which generates Ca 2+ signaling modulators from NAD +, by genetic or pharmacological inhibition. We show: A fully restored cardiac function. Fully restored NAD + levels concomitantly with normalized Ca 2+ signalling. Improved skeletal muscle performances in the severely affected dystrophin/utrophin‐deficient mice. Reduced Ca 2+ leak displayed by patients DMD myotubes treated with SARCLISA ®, a monoclonal anti‐CD38 antibody, suggesting a novel therapeutic strategy. Abstract : Duchenne muscular dystrophy (DMD) is characterized by muscle NAD + deficit and muscle Ca 2+ overload. In various dystrophic mouse models and a human DMD cell culture, we have targeted the multifunctional enzyme CD38, a NAD + glycohydrolase that generates Ca 2+ signaling modulators from NAD +, by genetic or pharmacological inhibition.